2021
DOI: 10.1109/access.2021.3080325
|View full text |Cite
|
Sign up to set email alerts
|

Segments Interpolation Extractor for Finding the Best Fit Line in Arabic Offline Handwriting Recognition Words

Abstract: In the last few years, deep learning-based models have made significant inroads into the field of handwriting recognition. However, deep learning requires the availability of massive labelled data and considerable computation for training or automatic feature extraction. The role of handcrafted features and their significance is still crucial for a specific language type because it is a unique way of writing the characters. These are primitive segments that describe the letter horizontally or vertically distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The results showed that there was a significant average pressure difference between the two. At the same time, stroke complexity, signature handwriting size, and handwriting recognition affected the average pressure [ 9 ]. By combining nonparametric test and t -test, Setyawati selected the ratio between the standard deviation and the average value of data such as writing time, handwriting peak speed, and pressure as the judgment basis.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that there was a significant average pressure difference between the two. At the same time, stroke complexity, signature handwriting size, and handwriting recognition affected the average pressure [ 9 ]. By combining nonparametric test and t -test, Setyawati selected the ratio between the standard deviation and the average value of data such as writing time, handwriting peak speed, and pressure as the judgment basis.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of Indian documents, thorough experimentations were performed on other corpus comprising in print and in-writing texts 8 . Other studies proposed the IFN/ENIT dataset to surmount the dearth of Arabic datasets easily accessible for researchers 9 and a popular literature Arabic/English dataset: Everyday Arabic-English Scene Text dataset (EvArEST) for Arabic text recognition 10 . Other researchers proposed Ekush dataset for Bangla handwritten text recognition 11 , Tamil dataset for in-writing Tamil character recognition utilizing deep learning 12 , 13 , DIDA dataset for detection and recognize in-writing numbers in ancient manuscript drawings dated from the nineteen century 14 .…”
Section: Background and Summarymentioning
confidence: 99%